Deforestation, Growth and Agglomeration Effects: Evidence From Agriculture in the Brazilian Amazon - Danilo Igliori (European Regional Science Association (ERSA), 2006)
The role of population growth and migration has been emphasized as a key variable to explain deforestation and land conversion in developing countries. In early studies a 'Malthusian' process is put forward to associate the growing demand for resources caused by larger populations in frontier areas. Recent empirical research has also focused on the role of population primarily as a measure for local demand and pressure over natural resources. The spatial distribution of human population and economic activities is remarkably uneven. At any geographical scale we find that different forms of agglomerations are pervasive. On the one hand, in central countries or regions, agglomeration is reflected in 'large varieties of cities as shown by the stability of urban hierarchy within most countries'. On the other, less developed regions faces a dynamic process where new agglomerations form and develop as a result of frontier expansion. The recent literature on spatial economics has emphasized the role of agglomeration and clustering of economic activities as fundamental causes of an enhanced level of local economic performance, creating externalities that cause firms to grow faster and larger than they otherwise would do. However, very little has been done to examine the presence of agglomeration economies on economic performance of agricultural activities. The Brazilian Amazon is perhaps one of the most interesting regions for analysing eventual relationships between agglomeration economies, economic growth and deforestation. In this paper we empirically examine whether an initial level of agglomeration impacts the subsequent economic growth and deforestation rates in the Brazilian Amazon. We also test whether congestion effects at the higher levels of agglomeration limit these impacts by a non-linear relationship. The regression estimates indicate that there is a significant non-linear association between the initial intensity of agglomeration with both growth and land conversion in subsequent periods. We also find evidence of other factors associated with growth and land conversion.
Keywords: 330